TGF‐β as a driver of fibrosis: physiological roles and therapeutic opportunities. Issue 4 (19th May 2021) - Budi, Erine H; Schaub, Johanna R; Decaris, Martin; Turner, Scott; Derynck, Rik
Abstract: Many chronic diseases are marked by fibrosis, which is defined by an abundance of activated fibroblasts and excessive deposition of extracellular matrix, resulting in loss of normal function of the affected organs. The initiation and progression of fibrosis are elaborated by pro‐fibrotic cytokines, the most critical of which is transforming growth factor‐β1 (TGF‐β1). This review focuses on the fibrogenic roles of increased TGF‐β activities and underlying signaling mechanisms in the activated fibroblast population and other cell types that contribute to progression of fibrosis. Insight into these roles and mechanisms of TGF‐β as a universal driver of fibrosis has stimulated the development of therapeutic interventions to attenuate fibrosis progression, based on interference with TGF‐β signaling. Their promise in preclinical and clinical settings will be discussed. © 2021 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.